Results of chemotherapy in 30 AIDS patients with symptomatic pulmonary Kaposi's sarcoma. Issue 10 (October 1994) - Cadranel, J L; Kammoun, S; Chevret, S; Parrot, A; Denis, M; Winter, C; Carette, M F; Rozenbaum, W; Akoun, G M; Mayaud, C M
Abstract : BACKGROUND--The aim of this study was to report the effects of a three-drug chemotherapy regimen in patients with symptomatic AIDS-related pulmonary Kaposi's sarcoma and to analyse prognostic factors for survival. METHODS--Thirty consecutive HIV seropositive patients with respiratory symptoms and proven pulmonary Kaposi's sarcoma were treated with the same therapeutic regimen comprising adriamycin (30 mg/m2), bleomycin (10 mg/m2), and vincristine (2 mg) administered intravenously once every four weeks. RESULTS--Two patients died during the first course of chemotherapy. In the other 28 cases dyspnoea improved and Pao2 rose despite minimal (n = 17) or no (n = 11) improvement in the chest radiographic appearance. The median survival from the beginning of chemotherapy was 6.5 months. Poor prognostic factors for survival were: (1) absence of cutaneous Kaposi's sarcoma; (2) previous opportunistic infection; (3) CD4 cell count < 100/microliters; (4) leucocytes < 3500/microliters; (5) haemoglobin < 10 g/dl; and (6) absence of radiological response. Of the 28 patients 24 experienced at least one episode of neutropenia which was associated with bacterial infection in 16 cases. CONCLUSIONS--Chemotherapy may improve respiratory impairment in patients with extensive pulmonary Kaposi's sarcoma but the outcome remains poor. The efficacy of chemotherapy may be limited by neutropenia.